Filler calcium carbonate industrial applications: the way for enhancing and reusing marble slurry - Marras, Graziella; Careddu, Nicola; Siotto, Giampaolo (Italian journal of engineering geology and environment, 2017)
<span data-sheets-value=""1":2,"2":"Since ancient times marble has been the most praised material due to its multi-use possibilities. The investigation conducted by the authors started several years ago with the aim to outline the study of industrial applications for marble dust deriving from marble processing plants as calcium carbonate. The matter of fact is that this stone slurry is composed primarily of calcium carbonate and has a great potential as secondary raw material or byproduct, although it has up to now been considered as waste and treated as such by their producers. Seeing as how calcium carbonate product specifications vary depending on the application, the marble sludge was submitted to a characterization in order to evaluate the compatibility with the specifications required by particular sectors. Firstly, mineralogical, physical and chemical determinations were carried out. Secondly, tests and analyses have been accomplished for the use of micronized calcium carbonate in building industry (brick, plaster and concrete making). More recently, the possibility of using micronized stone powder to produce different commodities for tyre industries has been studied. The data emerging from the analyses ensure that the sludge production can have a potentially high economic value and allow to go along with the concept of sustainable development."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">Since ancient times marble has been the most praised material due to its multi-use possibilities. The investigation conducted by the authors started several years ago with the aim to outline the study of industrial applications for marble dust deriving from marble processing plants as calcium carbonate. The matter of fact is that this stone slurry is composed primarily of calcium carbonate and has a great potential as secondary raw material or byproduct, although it has up to now been considered as waste and treated as such by their producers. Seeing as how calcium carbonate product specifications vary depending on the application, the marble sludge was submitted to a characterization in order to evaluate the compatibility with the specifications required by particular sectors. Firstly, mineralogical, physical and chemical determinations were carried out. Secondly, tests and analyses have been accomplished for the use of micronized calcium carbonate in building industry (brick, plaster and concrete making). More recently, the possibility of using micronized stone powder to produce different commodities for tyre industries has been studied. The data emerging from the analyses ensure that the sludge production can have a potentially high economic value and allow to go along with the concept of sustainable development.